명태 Gadus chalcogrammus 피부계의 미세해부학적 구조 - 김현진; 신소령; 김재원; 이정식; Hyeon Jin Kim; So Ryung Shin; Jae Won Kim; Jung Sick Lee (한국해양생명과학회지, 2023)
This study describes the light microscopical cell types and histochemical characteristics as a preliminary study for the research on integument of the walleye pollock Gadus chalcogrammus in accordance with the physiological and environmental changes. The lateral line of the integument surface showed a curve in the anterior part and was straight from the middle to the posterior part. Integument is composed of outer epidermis and inner dermis. The epidermis is a stratified layer composed of epithelial cells, mucous cells, and club cells. Epithelial cells are classified into squamous superficial cell, cuboidal intermediated cell and columnar basal cell. The thickness of epidermis was 122.9 ㎛, and the ratio of epidermis thickness to body length was 0.03%. The mucous cell and club cell of unicellular gland were mainly distributed in the apical and middle layer of epidermis. The mucous cell contained mucosal materials of acidic glycoprotein. The proportion of mucous cells and club cells were 21.3 (± 7.0)% and 4.0 (± 1.0)% of epidermal area, respectively. The dermis was dense connective tissue layer and composed of mainly collagen fibers. It also contained fibrocytes, blood vessels, melanophores and scales. 본 연구는 생리적, 환경적 변화에 따른 명태 Gadus chalcogrammus 피부계의 변화 연구를 위한 기초 연구로서 피부계의 구조, 구성 세포 종류 및 조직화학적 특징을 기재하였다. 측선은 전반부가 완만한 곡선형이었으며, 중반부터 후반부까지는 직선으로 나타났다. 피부는 상피층과 진피층으로 구성되며, 상피층은 다층으로 상피세포, 점액세포, 곤봉세포로 이루어져 있다. 상피세포는 표면층의 편평형 세포, 중간층의 입방형 세포, 기저층의 원주형 세포로 구성된다. 상피층의 두께는 122.9 ㎛, 체장에 대한 상피층의 두께 비율은 0.03%였다. 단세포선인 점액세포와 곤봉세포는 주로 상피층의 표면층과 중간층에 분포하며, 점액세포는 산성 당단백질의 점액물질을 함유하고 있었다. 상피층에서 점액세포와 곤봉세포의 분포비율은 각각 21.3 (± 7.0.)%와 4.0 (± 1.0)%였다. 진피층은 치밀결합조직으로 주로 콜라겐 섬유로 구성되며, 섬유세포, 혈관, 색소포, 비늘이 관찰되었다.